2008
DOI: 10.1242/jeb.018820
|View full text |Cite|
|
Sign up to set email alerts
|

The movements of limb segments and joints during locomotion in African and Asian elephants

Abstract: There was an error published in J. Exp. Biol. 211, 2735-2751 On p. 2740, in the section entitled 'Limb motion during normal walking', a character was missing in the second sentence such that the degree of incline of the forearm, forefoot and thigh segments at mid-stance was incorrectly given as 411 deg. rather than 4-11 deg. The text should have read:'At mid-stance, the forearm, forefoot and thigh segments were all relatively vertical (within 4-11 deg.), whereas the upper arm, shank and hindfoot segments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…The stride length of each limb was approximately 200 cm, ranging from 192.6 to 198.9 cm, with no significant difference between the fore and hindlimb on each side at a comfortable walking speed of average 1.1 ms -1 . This may confirm that elephants walk with a lateral sequence footfall pattern, and distribute their center of mass proportionally across all four limbs, as reported in previous studies [5][6][7]16] . It was somewhat surprising that in this study the average stride length on the right side was significantly longer than that on the left (P<0.05 for both fore limbs and hind limbs).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The stride length of each limb was approximately 200 cm, ranging from 192.6 to 198.9 cm, with no significant difference between the fore and hindlimb on each side at a comfortable walking speed of average 1.1 ms -1 . This may confirm that elephants walk with a lateral sequence footfall pattern, and distribute their center of mass proportionally across all four limbs, as reported in previous studies [5][6][7]16] . It was somewhat surprising that in this study the average stride length on the right side was significantly longer than that on the left (P<0.05 for both fore limbs and hind limbs).…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of elephant locomotion is limited, however, the studies of Hutchinson et al [6] , Ren et al [16] , and Genin et al [5] clarified the locomotor kinetic and kinematic characteristics of Asian elephants. They revealed that elephants, as with other quadrupeds, use a lateral sequence footfall pattern during walking to achieve the objectives of effective energy expenditure and minimal muscular work [5,6,16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Animals using a relatively columnar wrist and hand posture would have carpal joints that are in line with the hand and forearm, similar to limb joint position in large graviportal animals such as elephants (43). Supporting loads directly over more vertically-oriented forelimb joints during support phase explains the absence of posited bony adaptations to bending loads in gorillas and also permits more mobility at the joint (43).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, kinematics, ground reaction force determination, or both have been used in a variety of species such as elephants [33][34][35] , cattle 36 , horses [37][38][39][40] , dogs 4,[41][42][43][44][45] , cats 21,[46][47][48][49] , various rodents 3,8,50,51 , birds 4,[52][53][54][55] , and fish 56,57 (this list is by no means exhaustive). In the authors' experience, however, the use of mice is problematic given that mice are not easy to operantly condition to travel along a runway.…”
Section: Discussionmentioning
confidence: 99%